NATIONAL AND PATRIOTIC EDUCATION OF CHILDREN AND YOUTH: QUESTIONS OF STANDARDS AND INDICATORS - Zhanna Petrochko (National Academy of Educational Sciences of Ukraine, 2018)
The problem of monitoring the process of national-patriotic education in Ukraine has been updated. The purpose of the article is to substantiate the expediency and content of the standards and indicators of national-patriotic education of children and young people, which underlie the monitoring of this process. The necessity and various aspects of the contents of the standards of national patriotic education have been revealed; a list of effective measures as a key factor of the effectiveness of national patriotic education and recommended indicators of public opinion monitoring on patriotism have been presented. Besides the list of indicators of effectiveness of carrying out activities on national-patriotic education of children and youth is presented and supplemented by: number of prepared activist leaders who are ready to identify and implement initiatives of national-patriotic education; the dynamics of the number of young people involved in the activities of national-patriotic education; the proportion of young people involved in the activities of national-patriotic education in the village; the correspondence of the purpose and content of the measures to the values benchmarks, the content of the Strategy of national-patriotic education of children of youth in 2016-2020; monitoring (regularity of questionnaires) of public opinion on patriotism issues; polls of participants on the quality of the activities of national-patriotic education; innovation of the event, social effect and demand; engagement of partner resources; publicity of the project / event; reviews on social networks; possibility of dissemination of positive experience of project / activity realization.